2012
DOI: 10.3844/amjsp.2012.33.36
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Computer-Related Musculoskeletal Pain Among College Students-a Cross-Sectional Study

Abstract: Problem statement:In the recent years, there has been an increase in incidence of musculoskeletal complaints among college students. Potential risk factors for this might be increased use of computers. The purpose of this study was to examine among college students (a) the prevalence of musculoskeletal pain and (b) the association of musculoskeletal pain with computer use and physical activity performed during last one week. Approach: A cross-sectional study was performed among college students aged 19-27 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Rajagopal et al [13] reported high prevalence of MSP among Malaysian college students, but showed no association of MSP and computer use. Rajagopal study [13] had been done on a smaller sample size as mentioned in his study limitation. However, our results were in agreement with findings of other literature reviews [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajagopal et al [13] reported high prevalence of MSP among Malaysian college students, but showed no association of MSP and computer use. Rajagopal study [13] had been done on a smaller sample size as mentioned in his study limitation. However, our results were in agreement with findings of other literature reviews [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [13] investigated the prevalence of MSP among Malaysian college students and its relationship to computer use. This study reported high prevalence (90%) among females and (76%) male students, but showed no link of MSP to computer use.…”
Section: Introductionmentioning
confidence: 99%